"Babywearing" in the NICU: An Intervention for Infants With Neonatal Abstinence Syndrome. (December 2020) - Williams, Lela Rankin; Gebler-Wolfe, Molly; Grisham, Lisa M.; Bader, M. Y.
Abstract : Background: The US opioid epidemic has resulted in an increase of infants at risk for developing neonatal abstinence syndrome (NAS). Traditionally, treatment has consisted of pharmacological interventions to reduce symptoms of withdrawal. However, nonpharmacological interventions (eg, skin-to-skin contact, holding) can also be effective in managing the distress associated with NAS. Purpose: The purpose of this study was to examine whether infant carrying or "babywearing" (ie, holding an infant on one's body using cloth) can reduce distress associated with NAS among infants and caregivers. Methods: Heart rate was measured in infants and adults (parents vs other adults) in a neonatal intensive care unit (NICU) pre- (no touching), mid- (20 minutes into being worn in a carrier), and post-babywearing (5 minutes later). Results: Using a 3-level hierarchical linear model at 3 time points (pre, mid, and post), we found that babywearing decreased infant and caregiver heart rates. Across a 30-minute period, heart rates of infants worn by parents decreased by 15 beats per minute (bpm) compared with 5.5 bpm for infants worn by an unfamiliar adult, and those of adults decreased by 7 bpm (parents) and nearly 3 bpm (unfamiliar adult). Implications for Practice: Results from this study suggest that babywearing is a noninvasive and accessible intervention that can provide comfort for infants diagnosed with NAS. Babywearing can be inexpensive, support parenting, and be done by nonparent caregivers (eg, nurses, volunteers). Implications for Research: Close physical contact, by way of babywearing, may improve outcomes in infants with NAS in NICUs and possibly reduce the need for pharmacological treatment. See the video abstract for a digital summary of the study. Video Abstract Available at: https://journals.lww.com/advancesinneonatalcare/Pages/videogallery.aspx?autoPlay=false&videoId=38 Abstract : Supplemental Digital Content is Available in the Text.